Burnout and Maladjustment Among Employed Students - Drăghici, Gabriela-Lăcrămioara; Cazan, Ana-Maria (Frontiers in Psychology, 2022)
Stress and burnout are present in every aspect of an individual life, and the growing number of employed students raises certain concerns about their engagement in academic tasks and finishing their studies. Our paper aims to analyse the differences between student burnout in different contexts, work and academic related burnout and to examine the predictive role of burnout on academic maladjustment, including also test anxiety as mediator and occupational status as moderator. The sample consisted in 151 students from different universities in Romania. Consistent with previous studies, the results showed that academic burnout is higher than work-related burnout. High levels of test anxiety explain high level of academic burnout, which in turn explain a low level of academic adjustment. The results highlight the mediating role of anxiety in the relationship between academic burnout and academic maladjustment with occupational status as moderator. Future research could focus on the type of students’ job, the mediating relationship between self-efficacy and academic burnout and on the relationship between burnout and personality traits.